Perioperative management of patients with diabetes - Radkowski, Paweł; Kędziora, Bartosz; Eliszewska, Laura; Jackowska, Kaja; Mandziuk-Radkowska, Oliwia; Dawidowska-Fidrych, Justyna (Medical Studies/Studia Medyczne, 2023)
The prevalence of diabetes mellitus has been steadily increasing rapidly in recent years. Risk factors include obesity and lack of physical activity. Not only is it the most common endocrine disease in Europe, but also it is widely prevalent worldwide. Hyperglycaemia and diabetes were responsible for about 6.7 million deaths worldwide and 1.1 million deaths in Europe in 2021. Diabetes has a significant impact on the economy as well. This is a common disorder in surgical patients and proper anaesthesiology management of this disease is the single most important issue, though still poorly understood. Patients with diabetes mellitus have a higher risk of difficult intubation and aspiration. Diabetics undergoing surgery are particularly at risk of postoperative complications and increased mortality. In this review, the authors discuss the perioperative considerations in managing patients with diabetes as well as those without diabetes, albeit hyperglycaemic.